1997
DOI: 10.1007/s004330050072
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitamin E and cimetidine on peritonitis-induced lipid peroxidation

Abstract: To investigate the effects of acute fecal peritonitis on plasma and tissue lipid peroxidation and possible protective effects of vitamin E (Vit E) and cimetidine at 4 h in a rat peritonitis model, four groups were designated as: controls, peritonitis, Vit E and cimetidine. Plasma, liver, lung and kidney thiobarbituric acid reactive substances (TBARS) and conjugated diene (CD) levels were measured to monitor oxidative injury. The present fecal peritonitis model caused a significant elevation in liver TBARS; how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The role of reactive oxygen species (ROS) in peritonitis is controversial. Recently, several intestigators have observed protective effect of antioxidants against peritonitis‐induced lipid peroxidation in rats ( 42, 43). On the other hand, Kim et al ( 44) have suggested an important role of ROS in antimicrobial defences of the peritoneal cavity in experimental peritonitis.…”
Section: Discussionmentioning
confidence: 99%
“…The role of reactive oxygen species (ROS) in peritonitis is controversial. Recently, several intestigators have observed protective effect of antioxidants against peritonitis‐induced lipid peroxidation in rats ( 42, 43). On the other hand, Kim et al ( 44) have suggested an important role of ROS in antimicrobial defences of the peritoneal cavity in experimental peritonitis.…”
Section: Discussionmentioning
confidence: 99%